Circular economy business models and operations management - Lopes de Sousa Jabbour, Ana Beatriz; Rojas Luiz, Joao Victor [UNESP]; Rojas Luiz, Octaviano [UNESP]; Jabbour, Charbel Jose Chiappetta; Ndubisi, Nelson Oly; Caldeira de Oliveira, Jorge Henrique; Junior, Flavio Horneaux (Elsevier, 2019)
This article examines and conceptualizes the implications of the adoption of circular economy (CE) business models on operations management (OM) decision-making processes, in the areas of product design, production planning and control, and logistics/supply chains. A systematic literature review was conducted in order to identify and examine the following key areas: (1) the new demands faced by OM decision-making regarding changes in capability, work procedures, intra- and inter-organizational relationships and technologies; (2) the specific changes OM decision-making must make in order to support CE business models (based on the ReSOLVE framework); and (3) guidelines which will help designers and operations and logistics/supply chain managers develop the necessary skills to meet society and the global market's emerging demands. The findings of this research will allow operations managers to foresee the unfolding needs for capacity building in CE, and scholars can build on the results of this article to develop new research themes. Furthermore, this is the first article to describe the ways in which OM knowledge can support the transition towards the circular economy based on the perspective of dynamic capabilities.
Keywords: Circular economy; Logistics; Product design; Production planning; Sustainable operations; Sustainable supply chains